A systematic review of transoral robotic surgery and radiotherapy for early oropharynx cancer: A systematic review. (27th May 2014) - de Almeida, John R.; Byrd, James K.; Wu, Rebecca; Stucken, Chaz L.; Duvvuri, Uma; Goldstein, David P.; Miles, Brett A.; Teng, Marita S.; Gupta, Vishal; Genden, Eric M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To demonstrate the comparative effectiveness of transoral robotic surgery (TORS) to intensity modulated radiotherapy (IMRT) for early T‐stage oropharyngeal cancer. Data Sources The search included MEDLINE, EMBASE, CENTRAL, PsychInfo, CINAHL, and bibliographies of relevant studies through September 2012. Methods Studies included patients treated for early T‐stage oropharynx cancer with TORS or IMRT. Study retrieval and data extraction were conducted in duplicate and resolved by consensus. Treatment‐ specific details, as well as recurrence, survival, and adverse events, were collected. Methodologic quality for each study was appraised. Results Twenty case series, including eight IMRT studies (1, 287 patients) and 12 TORS studies (772 patients), were included. Patients receiving definitive IMRT also received chemotherapy (43%) or neck dissections for persistent disease (30%), whereas patients receiving TORS required adjuvant radiotherapy (26%) or chemoradiotherapy (41%). Two‐year overall survival estimates ranged from 84% to 96% for IMRT and from 82% to 94% for TORS. Adverse events for IMRT included esophageal stenosis (4.8%), osteoradionecrosis (2.6%), and gastrostomy tubes (43%)—and adverse events for TORS included hemorrhage (2.4%), fistula (2.5%), and gastrostomy tubes at the time of surgery (1.4%) or during adjuvant treatment (30%). Tracheostomy tubes were needed in 12% of patients at the time of surgery, but most were decannulated prior to discharge. Conclusion This review suggests that survival estimates are similar between the two modalities and that the differences lie in adverse events. Laryngoscope, 124:2096–2102, 2014